(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
The consumption Ultra-Processed Foods (UPF) continues to rise among adolescents, including students in Islamic boarding schools. Easy access to snacks high in sugar, salt, and fat (SSF), limited nutrition education, and insufficient provision of healthy meals make santri vulnerable to dietary patterns that increase the risk of obesity and chronic diseases, including cancer. This community service program aimed to improve the knowledge of students regarding cancer risks associated with UPF consumption, as well as their skills in preparing healthy non-UPF meals. The method employed was a participatory empowerment approach through educational activities and practical training conducted from October to November 2025 at Pondok Pesantren Tadabbrur Al Qur’an. The activity stages included socialization, nutritional status assessment, delivery of educational materials on cancer risk and UPF, and training on healthy food preparation. Evaluation was carried out through pre-test and post-test assessments and participant feedback. The results showed from 30 participants, UPF consumption among students remained high, dominated by flavored UHT milk, instant noodles, sweet biscuits, and packaged beverages. The educational sessions significantly improved students’ knowledge scores (p= 0.000). This activity demonstrates that educational and practical interventions can effectively enhance healthy eating understanding and practices within the pesantren environment, thereby serving as a potential preventive strategy against chronic disease risks in the future. We suggest Islamic boarding schools can provide supervision on UPF consumption by students and the menu recommendations given in Non-UPF Cooking Demonstrations can be used as a reference in food service for students.